Citizenship(s) and sexuality(s) of childhoods and adolescences in the Comprehensive Sexual Education Law 26.150/06: towards a transformation of the school public sphere? (Praxis Educativa, 2023)
Within the democratic context of the recent incorporation of childhoods and adolescences as subjects of rights in Argentine legislation, the Law on Comprehensive Sexual Education 26.150/06 was debated during the years 2005 and 2006. In this article, we present two of the discussions that provoked divergent arguments in the National Congress. In the first place, the tension around the autonomy-heteronomy of childhoods and adolescences in regards to access to comprehensive sexual education. Secondly, the teaching approaches of sexual education -moral, biomedical and integral- in the context of a hetero-cis-normative system, which were used for the state regulation of sexuality. Conceiving childhoods and adolescences as political subjects implies rethinking the exercise of citizenship and the public school sphere where their interests, curiosities, questions, certainties, doubts, and fears, among others, are expressed in relation to sexuality; these are other questions that will thus be investigated in this article.
Keywords: citizenship; sexuality; political participation; children and adolescents; sex education